SEMEADORES DISSONANTES: IMIGRANTES E POLICIAIS NA PROVÍNCIA DO PARANÁ - SÉCULO XIX (Revista de História Regional, 2007)
This study discusses some aspects of the contact between the imigrants and the national population, in the second half of the 19th century. It is distinguished here the daily experience of these groups as an important element for the definition of the governmental action. The official proposes related to the maintenance of public security were continuously changed, with tensions caused by the gathering of imigrant population near cities and small tows and by the conflictual situations which were going on that time. The ideals of progress and civilization, the exaltation of "idoneous" people, the pacific and harmonious way of living, were associated to the official culture.